Invasive cerebral phaeohyphomycosis in a Chinese boy with CARD9 deficiency and showing unique radiological features, managed with surgical excision and antifungal treatment. (June 2021) - Lai, Sophie H.Y.; Duque, Jaime S. Rosa; Chung, Brian Hon-Yin; Chung, Tom Wai-Hin; Leung, Daniel; Ho, Ronnie Siu-Lun; Lee, Raymand; Poon, Rosana W.S.; Chua, Gilbert T.; Cheong, Kai-Ning; Chui, Martin Man Chun; Lee, Mianne; et al.
Highlights: Isolated cerebral phaeohyphomycosis may require a focus on CARD9 deficiency. Radiological imaging alone cannot differentiate cerebral fungal lesions from tumors. Paired CSF and serum voriconazole levels are useful in treating cerebral fungal infection. Abstract: We report this rare case of cerebral phaeohyphomycosis in a previously healthy Chinese boy, who was found to have caspase recruitment domain family member 9 (CARD9) deficiency. Initial radiological features suggested a neoplastic cerebral lesion, while histopathological examination supplemented by internal transcribed sequencing (ITS) of cerebral tissue confirmed the diagnosis of phaeohyphomycosis. He was treated with intravenous (IV) liposomal amphotericin B and voriconazole, guided by plasma and cerebrospinal fluid (CSF) level monitoring at drug initiation. At the 1 year follow-up, the patient demonstrated near complete neurological and radiological recovery.